Smart Contracts and the Challenges of Conflict of Laws in Digital Space - Khalifa, Attia Suleiman; Samad, Nashwan Salah (Indonesian Journal of Law and Economics Review, 2025)
General Background: Blockchain-based smart contracts have revolutionized global transactions by enabling automatic, transparent, and decentralized execution of agreements. Specific Background: Despite their efficiency, these digital instruments challenge traditional private international law, particularly regarding jurisdiction, applicable law, and enforceability in cross-border contexts. Knowledge Gap: Existing legal systems, especially in the Middle East, lack comprehensive frameworks to address decentralized contracting and blockchain-based evidence. Aims: This study critically examines the intersection between smart contracts and conflict of laws in digital environments, focusing on Iraq’s legal framework and regional comparison with the EU and the US. Results: The analysis reveals that while the EU has developed coherent regulatory models such as MiCA and the Data Act, and several US states have recognized smart contracts’ validity, Iraq’s Civil Code of 1951 remains inadequate to regulate automated digital agreements. Novelty: The paper proposes a unified legal model integrating UNCITRAL’s 2024 Model Law on Automated Contracting, regional cooperation through the Arab League and GCC, and legislative reforms in Iraq to recognize blockchain evidence. Implications: Implementing such a framework would harmonize technological progress with legal certainty, enhance cross-border trust, and position Iraq and the Middle East within the global digital economy.Highlight : Analyzes the intersection of smart contracts and conflict of laws in digital space. Examines Iraq’s outdated legal framework amid rapid technological change. Suggests adopting international models and regional cooperation for legal reform. Keywords : Smart Contracts, Blockchain, Conflict of Laws, Private International Law, Jurisdiction, Iraq.